ACID-BASE PROPERTIES OF ALKYLENEDIAMINETETRA (METHYLENEPHOSPHONIC) ACIDS - Kozachkova, Oleksandra; Tsaryk, Nataliya; Pekhnyo, Vasyl; Trachevskij, Volodymyr; Kocharovska, Olga; Palchyk, Oleksii (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2023)
The acid-base characteristics of ethylenediaminetetra(methylenephosphonic) (edtmp), tetramethylenediaminetetra(methylenephosphonic) (tetdtmp) and pentamethylenediaminetetra(methylenephosphonic) (pendtmp) acids were investigated by means of pH-potentiometry and 31P NMR spectroscopy. Calculated and estimated values of acid dissociation constants (pK) for edtmp (рК1<2, рК2<2, рК3=3.07, рК4=5.17, рК5=6.52, рК6=7.97, рК7=9.65, рК8=10.94), for tetdtmp (рК1<2, рК2=4.48, рК3=5.34, рК4=6.13, рК5=6.66, рК6=10.08, рК7~11.4, рК8~11.5) and for pendtmp (рК1<2, рК2=4.22, рК3=5.56, рК4=6.16, рК5=7.66, рК6=10.99, рК7~11.5, рК8~11.6) were obtained. The values of the acid dissociation constants indicate a decrease in the acidity of phosphonic groups and an increase in the basicity of amino groups with increasing hydrocarbon chain length between the two nitrogen atoms in the edtmp, tetdtmp, and pendtmpseries. Based on the values of the calculated constants for the formation of anions of tetraphosphonic acids, diagrams of the distribution of their equilibrium concentrations depending on pH were constructed, which indicate the state of acid-base equilibrium, the charge and the ratio of concentrations between anions with different degrees of protonation at certain pH values. According to the data of 31P NMR spectroscopy, the formation of intramolecular hydrogen bonds between the deprotonated oxygen atoms of one amino(methylphosphonic) group with protonated nitrogen atom of another amino(methylphosphonic) group was established in the case of edtmp. In the case of pendtmp and tetdtmp, the formation of intermolecular hydrogen bonds between distant amino(methylphosphonic) groups is impossible due to the presence of steric hindrances.